Analisis Risiko Rantai Pasok Material Terhadap Keterlambatan Pelaksanaan Proyek Konstruksi - Hendi Kurniawan; Ida Ayu Ari Anggraeni (Rekayasa Sipil, 2020)
The uncertainty of the supply chain in the process of procuring building materials can be a risk that results in delays in the implementation of construction projects. This study aims to analyze the material supply chain risks that affect delays in the implementation of construction projects. Supply chain risks are classified from Supply, Control, Demand, and Process. Data collection by survey method and respondents selected by purposive sampling method. The analysis used is the AHP method. The risk response is confirmed to the expert by the interview method. The results of the risk assessment found that the late delivery of material due to non-current financial problems with FR = 0.703 was the most risky factor resulting in project development delays.